PERAN FAKULTAS HUKUM DALAM PENYIAPAN KESIAPSIAGAAN NASIONAL MENANGGULANGI TERORISME DI ERA REVOLUSI INDUSTRI 4.0 - Marthsian Yeksi Anakotta; Wahyu Krisnanto; R.R. Elizabeth Marcia Titi Handayani (Faculty of Law, Parahyangan Catholic University, 2023)
The use of information technology for the crime of terrorism is marked by a revolution in the modus operandi of crimes, starting from conventional to modern technological methods. Even though so far Indonesia has handled it fairly well, the crime of terrorism will continue to develop in other ways so that a continuous development of the ways to handle the crime is also needed through the preparation of what is called ‘National Preparedness’. This research begins with the examination of the the crime of terrorism through a legal (criminal) and information technology perspective of the institution of higher education in law (Faculty of Law) in a planned, integrated, systematic and sustainable manner. This study aims to identify and understand the role of higher education institutions, especially Faculty of Law, in preparing Indonesia's National Preparedness to tackle terrorism crimes. Researchers use empirical juridical research by collecting primary data through in-depth interviews. The result is that higher education, especially the Faculty of Law, plays a role in supporting the preparation of National Preparedness through the implementation of legal higher education by integrating criminal law studies with the field of terrorism and the field of technology in implementing the Tridharma. Terrorism studies from a legal (criminal law) and information technology perspective can serve as a reference for the Government of Indonesia in preparing National Preparedness to tackle terrorism crimes.